Cinema and the teaching of art in Brazil: a look at modernist conceptions and experiences - Lima, Sidiney Peterson F. de [UNESP] (Univ Valencia, Dept Prehistoria & Arqueologia, 2020)
This paper aims to present and discuss some of the practices developed in the field of art teacher training, within the scope of the Intensive Course of Art in Education (CIAE), pointing out, in particular, the presence of cinema as an important artistic language in the trajectory of formation. Initially, based on a historical context, based on the studies of researcher Ana Mae Barbosa (2015), we conducted a discussion about the relations between cinema and education, considering the readings about cinema through projects in the period of the New School Movement (1920, 1930), highlighting the actions developed by the poetess and educator Cecilia Meireles. With the present work we aim to broaden the ideas and perceptions about the history of cinema and education in Brazil, especially in the field of art teacher training, considering the CIAE experience.Y
Keywords: cinema; art in education; history; teacher training; CIAE